2000
DOI: 10.1385/bter:73:1:47
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and Malondialdehyde Content and Glutathione Peroxidase Activity in Maternal and Umbilical Cord Blood and Amniotic Fluid

Abstract: Placenta tissue may be a major source of lipid peroxidation products in pregnancy. It was proven that placental peroxidation activity increases with gestation. Selenium (Se), as an essential constituent of glutathione peroxidase (GSH-Px), takes part in the reduction of hydrogen peroxides and lipid peroxides. Malondialdehyde (MDA) is a major breakdown product split off from lipid peroxides. In this study, Se and MDA content and GSH-Px activity were measured in blood and plasma taken from 20 apparently healthy n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(69 citation statements)
references
References 16 publications
5
62
1
1
Order By: Relevance
“…Moreover, oxidative stress is known to increase during pregnancy, even in a normal pregnancy (Myatt et al, 2000;Myatt and Cui, 2004). It has also been reported that the MDA level is higher in pregnant women than in non-pregnant women (Morris et al, 1998;Mihailović et al, 2000). In other words, pregnant women can Fruit and vegetable and PAH exposure with MDA H Kim et al easily be exposed to oxidative stress, possibly as a result of PAH exposure while cooking and as a result of conception itself.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, oxidative stress is known to increase during pregnancy, even in a normal pregnancy (Myatt et al, 2000;Myatt and Cui, 2004). It has also been reported that the MDA level is higher in pregnant women than in non-pregnant women (Morris et al, 1998;Mihailović et al, 2000). In other words, pregnant women can Fruit and vegetable and PAH exposure with MDA H Kim et al easily be exposed to oxidative stress, possibly as a result of PAH exposure while cooking and as a result of conception itself.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional assays to measure lipid peroxidation have relied on the thiobarbituric acid (TBA) assay, which involves adding TBA to the sample and colorimetrically measuring the resultant reactive substances (TBARS) [22,23]. The TBA test is calibrated with MDA.…”
Section: Markers Of Lipid Peroxidationmentioning
confidence: 99%
“…Many studies have compared biomarkers of oxidative stress in normal pregnant women and nonpregnant control subjects [16,17,22,23]. Results of such studies suggest that erythrocyte or plasma MDA and lipid peroxides are generally higher during the second trimester [23] as well as late in gestation [16,22,23]; higher levels of salivary 8-isoprostane concentrations (but not plasma) have been noted during the second trimester [17].…”
Section: Oxidative Stress and Antioxidant Status In Normal Pregnancymentioning
confidence: 99%
“…64 Some studies have revealed that serum selenium concentrations decreased throughout pregnancy edir. 65,66 In a study by Mokheber et al, selenium supplement resulted in a notable increase in average serum selenium concentration and average EPDS score was significantly lower. 67 These findings support the notion that selenium supplement during pregnancy can be an effective approach in preventing postpartum depression.…”
Section: Seleniummentioning
confidence: 98%